Sumbo yoro sé ! - Camille Devineau (Ateliers d'Anthropologie)
In Burkina Faso, the character of the Bwaba griots’ mask dance, the sumbopwa, shows the influence of bush spirits—invisible entities—over humans. Sumbo yoro se! “The mask dance is good!” This exclamation announces what the Bwaba designate as the “strength” that the dancer’s movements show. This “strength” incudes two complementary aspects: physical strength and the strength given by “the invisible”, namely the bush spirits’ ability to act upon mask wearers, and therefore upon the human world. It is an inspiration received from the bush spirits that enables mask wearers to perform feats all night long. They are then “no longer quite themselves” and display abilities reaching the limit of the human in order to approach that of the bush spirit. For the Bwaba, the bush spirits’ involvement in danced performance primarily signifies that they appreciate the ritual. The character of the mask dance therefore reveals the link that unites humans and bush spirits, the bush spirits’ favourable disposition towards humans, as well as the power that humans draw from them.